Determination of Microcytic Hypochromic Anemia (MCHC) for Hemoglobin Variants and Hemoglobinopathies by Using High Performance Liquid Chromatography (HPLC) - Kaustubh Vilasrao Kharche; Arvind Bhake (Challenges and Advances in Pharmaceutical Research Vol. 4, 2022)
The present study has been undertaken as the anemia is the most prevailing and commonly treated clinical state that is managed by numerous nutritional supplements without much being done to know the underlying etiology or without evaluation of hemoglobin for its abnormalities. Clinicians encounter a morphological class of anaemia known as Microcytic hypochromic anaemia (MCHC), also known as low cell volume anaemia, in modern practice, which has a variety of underlying etiologies. Iron deficiency anaemia, beta thalassemia trait, hemoglobinopathies caused by Hb E, Hb D, Hb C, and other factors are among the underlying causes. So, before beginning treatment, we must first screen haemoglobin for variations and aberrant hemoglobins. Methods: This is an observational (Prospective and Retrospective) study carried out in Department of Pathology, JNMC, Sawangi (Meghe), Wardha. Blood samples of 100 patients will be evaluated by High performance liquid chromatography Bio-Rad variant to look for various patterns of hemoglobin involved and the hemoglobinopathies associated with it. The observations will be made in accordance with the objectives and tallied before being subjected to statistical tests to determine their significance and conclusions. The conclusion will be based on the findings for study of protocol